Pengaruh Model Pembelajaran Blended Learning Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Akidah Akhlak Kelas XI MIA 3 DI MAN 2 Garut - Maria, Anly; Fauziah, Neng Mita (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
The Akidah Akhlak subject for Grade XI MIA 3 at MAN 2 Garut has faced challenges with fully online learning, particularly during the pandemic. Students often scored below the minimum competency standards (KKM), were less active during the learning process, and exhibited a lack of discipline, such as attending lessons late. To address these issues, the blended learning model is proposed as a suitable solution. This model integrates both online and offline learning, with each accounting for 50% of the instructional time. Blended learning is expected to enhance students' academic performance across cognitive, affective, and psychomotor domains. The objectives of this study are to: (1) describe the academic performance profile of students in the Akidah Akhlak subject for Grade XI MIA 3 at MAN 2 Garut, (2) examine the implementation process of the blended learning model in the Akidah Akhlak subject, and (3) assess the impact of the blended learning model on students' academic performance in this subject. The research employs a descriptive survey method, gathering data and information about the studied phenomena through questionnaires, observations, interviews, and document analysis. Questionnaires were distributed to 20 respondents, and data processing involved statistical analysis. The research findings indicate that the blended learning model received an average score of 4.1, placing it in the "very high" category (4.01-5.00 scale), and another average score of 3.6, categorizing it as "high" (3.01-4.00 scale). Student performance in the Akidah Akhlak subject averaged at 4.3, also in the "very high" category, with another score of 3.9, categorized as "high". Statistical tests revealed that the blended learning model accounted for 44.9% of the variance in student performance. Furthermore, t-test results showed a t-value of 3.78, exceeding the t-table value of 1.73. Consequently, the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. These results confirm a significant influence of the blended learning model on student performance in the Akidah Akhlak subject. Keywords: Blended Learning Model, Student Academic Performance, Akidah Akhlak